P152 The Relationship Between Educational Qualifications, Access To Information Technologies And Clinical Outcomes In Patients With Acute Exacerbation Of Copd (aecopd). (10th November 2014) - Wijayarathna, R; Suh, ES; Mandal, S; Hart, N
Abstract : Introduction and objectives: Although socioeconomic factors are known to influence clinical outcome in COPD patients, few studies have addressed the impact of educational attainment. This is particularly relevant in light of the fact that telehealth, using often complex technologies, are increasingly used in the management of chronic diseases. We therefore aimed to ascertain the proportion of patients hospitalised with AECOPD who have formal educational qualifications and access to information technologies. Method: Clinical and physiological data were prospectively gathered from consecutive patients admitted to a metropolitan teaching hospital with AECOPD between April and December 2013. Patient data were analysed according to the possession of educational qualifications, and access to a personal computer and the internet. Results: 100 patients were admitted with AECOPD (40% female, age 70.5 ± 9.3 years). 51% of patients lived alone, 38% were current smokers with a FEV1 0.70 ± 0.39 L at admission, and 13% were receiving long term oxygen therapy. Median symptomatic days prior to admission was 4.0 (IQR 1 to 14), with an annual admission frequency of 2.0 (IQR 1 to 6). 14% of patients had access to both a computer and the internet. Patients with no access to these technologies were older (71.2 ± 9.2 vs. 64.8 ± 7.7 years, p < 0.02). Patients with no educational qualifications had a lower%predicted FEV1 (31.2 ± 23.6 vs. 38.7 ± 20.9, p < 0.05), and were less likely to have access to information technologies (7% vs. 93%, p < 0.05). They were more likely to be readmitted within 28 days (11% vs 3%, p=ns), but presented with a lower symptom burden on admission as measured by the numerical rating scale (3.6/10 vs. 5.0/10, p=ns). Conclusion: These data suggest there may be difficulties in implementing the use of telehealth within this metropolitan COPD population. Only 14% had access to a computer and the internet. Patients with no educational qualifications had worse spirometry at admission, but surprisingly a lower symptom burden. This may be due to the fact that those with educational qualifications may have a greater awareness of the symptoms of an exacerbation, and therefore present to hospital at an earlier stage.